Schemes of Arrangement in terms of Chapter 5 of the Companies Act 71 of 2008 - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2021)
Dissertation (LLM (Corporate Law))--University of Pretoria, 2020.